PENGARUH PERPUTARAN TOTAL ASET DAN PERPUTARAN PERSEDIAAN TERHADAP RETURN ON ASET PADA PERUSAHAAN SEKTOR CONSUMER NON – CYCLICALS YANG TERDAFTAR DI BEI - Wulan Nur Annisa; Asep Suherman (Fakultas Ekonomi dan Bisnis, Universitas Wiraraja Madura, 2024)
The purpose of this study is to investigate the impact of total asset turnover (TATO) and inventory turnover (ITO) on return on asset (ROA) for companies in the consumer non-cyclicals sector listed on the Indonesia Stock Exchange (BEI). The population in this study consists of companies in the consumer non-cyclicals sector listed on the BEI from 2020 to 2023. The sampling method used is purposive sampling, and 25 companies were obtained as samples. The data analysis technique used includes classical assumption tests (Multicollinearity, Heteroscedasticity, and Autocorrelation tests), Multiple Linear Regression Analysis, Hypothesis Testing (t-test and F-test), and Coefficient of Determination. The data processing in this study uses SPSS software for windows version 27. The results of the testing show that total asset turnover (X1) has a positive effect on ROA (Y) with a t-statistic value of 2.303 > t-table value of 1.98472 and significance level of 0.024 < 0.05. On the other hand, inventory turnover (X2) does not have an effect on ROA (Y) with a t-statistic value of 1.401 < 1.98472 or less than the t-table value. Based on the results from the coefficient of determination table, the adjusted R² value is 0.076. This means that the ability of independent variables such as total asset turnover, accounts receivable turnover, and inventory turnover in explaining dependent variable ROA is 7.6%, while 92.4% is explained by other variables not investigated in this study.